2010
DOI: 10.1254/jphs.09r13fm
|View full text |Cite
|
Sign up to set email alerts
|

The Forefront for Novel Therapeutic Agents Based on the Pathophysiology of Lower Urinary Tract Dysfunction: Ameliorative Effect of Solifenacin Succinate (Vesicare®), a Bladder-Selective Antimuscarinic Agent, on Overactive Bladder Symptoms, Especially Urgency Episodes

Abstract: Abstract. Overactive bladder (OAB) syndrome is a common condition that is most often observed in the elderly. Pharmacological treatment with muscarinic receptor antagonists has been most widely used for OAB. An antimuscarinic agent, solifenacin, showed the highest affinity for the muscarinic M 3 receptor, which mediates urinary bladder contraction. In preclinical studies, solifenacin exhibited a highly bladder-selective profile compared with other antimuscarinic agents. Solifenacin was also shown to increase b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…It was thus inferred that in addition to the antimuscarinic activity, the Ca 2+ channel-antagonizing activity might also contribute to the control of ACh-induced urinary frequency. In the ACh-induced urinary frequency model, the antimuscarinic agents used in this study were demonstrated to cause a dose-dependent increase in the micturition weight; this finding was consistent with previously reported data obtained in a rat model of cerebral infarction (16).…”
Section: Discussionsupporting
confidence: 92%
“…It was thus inferred that in addition to the antimuscarinic activity, the Ca 2+ channel-antagonizing activity might also contribute to the control of ACh-induced urinary frequency. In the ACh-induced urinary frequency model, the antimuscarinic agents used in this study were demonstrated to cause a dose-dependent increase in the micturition weight; this finding was consistent with previously reported data obtained in a rat model of cerebral infarction (16).…”
Section: Discussionsupporting
confidence: 92%
“…Solifenacin succinate is a competitive muscarinic receptor antagonist that blocks specifically M3 receptors on the urinary bladder, and thus is indicated to manage the OAB syndrome in adults [2]. The validation process has shown that our assay was specific, accurate, precise and reproducible.…”
Section: Discussionmentioning
confidence: 94%
“…The sudden involuntary contraction of the urinary bladder, caused by the pathophysiological mechanisms of the OAB syndrome, results in the clinical presentation of urgency, frequency and nocturia that may or may not be accompanied with incontinence [2]. The activation of the parasympathetic nervous system, and thus the muscarinic receptors on the smooth muscles of the bladder, mediates these annoying symptoms of the OAB syndrome [3].…”
Section: Introductionmentioning
confidence: 99%
“…A significant increase in M2R and M3R immunoreactivity in myofibroblasts-like cells was found in bladder specimens from patients with idiopathic DO (IDO) as compared with that in controls, furthermore showing a significant correlation with the urgency score [13]. It has been also reported that afferent nerves are located adjacent to the urothelium, and stimulation of MRs expressed on the urothelium may contribute to the activation of afferent nerves via non-neuronal ATP release, thus reducing urgency [14]. Activation of MRs in the urothelium releases substances that modulate afferent nerves [15].…”
Section: Muscarinic Receptorsmentioning
confidence: 99%